Cybercrime Victimisation and Polyvictimisation in Finland: prevalence and Risk Factors - Näsi, Matti (European journal on criminal policy and research, 2023)
This study examines the prevalence of different types of cybercrime victimisation and their shared risk factors among the population of Finland. We examine how respondents’ socio-economic background variables, past offline victimisation experiences, online activity, user skills, and protective measures impact the risk of the most common forms of online victimisation and online polyvictimisation. Our nationally representative survey data were collected from 5455 Finns aged 15 to 74 years (response rate 39%) as part of the Finnish National Crime Survey in 2018. According to our findings, the five most common forms of victimisation were malware, harassment, sexual harassment, hacking, and fraud. Online routines and exposure to potential offenders, along with past offline victimisation experiences, served as notable risk factors for a range of different victimisation experiences online. Our findings show slightly different SES risk factors for victimisation of different online offences, thereby indicating the diverse nature of different types of online victimisation. Our findings also show that young age, better financial situation, high internet use, and user skills, along with past offline victimisation of property crime and violence, associate with increased risk of online polyvictimisation. High user protection decreased the risk of online polyvictimisation.